Decoding strategies for stigma reduction in substance use disorder: A qualitative synthesis utilizing the theoretical domain and behavior change wheel frameworks - Abhishek Ghosh; Kshitiz Sharma; Arshia Sood; Babita Sharma; Blessy B. George (Indian Journal of Psychiatry, 2025)
Background: People with substance use disorders (PLSUD) face significant stigma, impeding treatment. Psychosocial interventions could reduce stigma, but the underlying mechanisms are unclear. Aim: This review analyzed authors’ behavioral explanations supporting stigma-reduction outcomes and explored links between these mechanisms and behavior change. Methods: A search was conducted through PubMed, Google Scholar, and a cross-reference search of the published systematic reviews on PLSUD. Inclusion criteria encompassed clinical trials targeting various populations and employing diverse intervention types. Data extraction and thematic analysis were performed using the Theoretical Domain Framework (TDF) to classify emergent themes and codes. The Behavior Change Wheel (BCW) framework was applied to understand the potential behavior change mechanism. Results: Of the 670 initially identified studies, 29 met the inclusion criteria. Most were from the US. These studies represented diverse intervention types, including social contact, psychoeducation, and peer support programs. Thematic analysis revealed 17 themes. Key themes included awareness building, social contact, and emotion processing. Awareness-building efforts targeted self-awareness, public perceptions, and societal expectations, while social contact interventions focused on direct interactions and sharing lived experiences. Strategies like mindfulness and meta-cognitive approaches were identified to aid emotion processing and cognitive reappraisal. The themes were categorized into ten TDF domains. “Knowledge” was the most common captured domain. The BCW framework surmised the interrelationship within domains and between domains and capability-motivation-opportunity. Conclusion: Psychosocial interventions for stigma reduction in PLSUD operate through multifaceted mechanisms. Understanding these mechanisms is crucial for designing effective interventions and addressing the complex dynamics of stigma surrounding SUDs.